A Complete Course in Structuring COBOL Programming - Molluzzo John C (Wadsworth Publishing Company, 1989)
Basic COBOL, Introduction, Writing a Simple Report, Arithmetic and Editing, Decision Making in COBOL: Data Validation, Tables and Table Searching, File Processing in COBOL, Sequential File Processing: Sorting and Control Brakes, Sequential File Processing: Inquiry and Update and Merge, Indexed File Processing, Relative File Processing, String Manipulation and Subprograms, Appendices, Index.